Mapping buried utilities in difficult environments - Zhang, Penghe (2018)
There is a large number of underground utilities buried in urban areas, which is one of the most complex networks in the world. It has been estimated that only 50% of buried utilities are accurately recorded. However, failure to identify accurately the location of existing buried utilities results in numerous practical problems, costs and dangers for utility owners, contractors and road users. The underground utilities positioning accuracy requirement is 100 mm for both the accuracy of positioning system and the accuracy of detection devices. While the accuracy up to 300 mm would be acceptable for many respondents.